Church growth theology - Habeahan, Sampitmo (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2023)
Jesus established the church in whom there is the hope of cross-growth. Church growth involves bringing people to Jesus who do not have a personal relationship with God. Church growth has to do with bringing souls to Jesus. So by its nature church growth includes the study of expansion, planting and multiplication, function and health of the church. There are generally two views on who is responsible for and expands church growth. One side of the responsibility is in the hands of the servants of God but on the other hand it is the responsibility of the people of God together. These two opinions need a correct understanding of the theology of church growth. So, whose responsibility is church growth? Is it only the servants of God, or does the entire church community also participate? Based on the formulation of the problem, the research title emerged, namely Theology of Church Growth. In this research, only the philosophy of church growth itself is discussed. The purpose of the research is to look at the principles of church growth and its philosophy. The object of research is church growth and the principles of church growth theologically. The research method is done by review literature that has existed before. The results of the research are: the basis of church growth is the Bible, there are two types of church growth in quality and quantity. The factors of church growth are caused by, having a burden in service, the work of the Holy Spirit, praying people who obey God in evangelism. This means that church growth itself is the work of the triune God. A growing church is God's desire, therefore people are responsible for the growth of the church.